The Place of Shareholder Activism by Institutional Investors in Georgian System of Corporate Governance and Its Influence on International Merger Transactions - Ramishvili, Ana (Journal of Law, 2017)
Institutional investors, in the course of the international mergers and acquisitions deals, play the particular role and the function. Increase of the role of institutional investors has been entailed with establishment of shareholder activism as the efficient mechanism for improvement of the corporate governance. The activist, by means of consideration of the nature and the forms of the types of the shareholders and the activism thereof, strives to define the feasibility of establishment of shareholder activism practice in Georgian companies and to demonstrate the interdependence between the institutional shareholder activism and the effective protection of the rights of minority shareholders. The article outlines the basics forming due pre-conditions for development of shareholder activism, which serves as a real opportunity for institutional shareholder activism to become the integral part of Georgian system of corporate governance. The role of the institutional investors, especially of the foreign institutional investors is manifested in exercise of the facilitative function, which in its turn makes the convergence of the corporate governance achievable. Alternative investment funds, through arbitrage transactions and activism related with appraisal of the stock shares, which have already become the integral parts of their investment strategy, facilitate to increase of the transaction price and fair valuation of the shares appurtenant to the minority shareholders. The institutional shareholder activism, based on the surveys, facilitates to extension of the rights of the minority shareholders and effective realization thereof.